Feeding during therapeutic hypothermia is safe and may improve outcomes in newborns with perinatal asphyxia. (12th December 2022) - Alburaki, Wissam; Scringer-Wilkes, Maxine; Dawoud, Fady; Oliver, Norma; Lind, Janice; Zein, Hussein; Leijser, Lara M.; Esser, Michael J.; Mohammad, Khorshid
Abstract: Objective: We assessed the impact of early enteral feeding introduction during therapeutic hypothermia on time to reach full enteral feeding (FEF) and other feeding related outcomes in infants born at ≥35 weeks gestational age and diagnosed with moderate to severe Hypoxic-Ischemic Encephalopathy. Methods: A prospective cohort with historical control study, conducted on infants admitted to the Alberta Children's Hospital level III NICU in Calgary between January 2013 and December 2018. Infants were divided into 2 groups: (1) unfed group (UG), which was kept nil per os during the 72 h of therapeutic Hypothermia (TH), with subsequent introduction of feeding and gradual increase to FEF; (2) fed group (FG), which received feeding at 10 mL/kg/day during TH then increased gradually to FEF. Groups were compared for time to FEF and the type of milk they were being fed on discharge. Other gut related health risks such as NEC and sepsis were examined. Results: During the study period, 146 infants received therapeutic hypothermia, of whom 75 in the UG and 71 in the FG. The FG compared to the UG received the first feed sooner after TH initiation (median 57 vs. 86.5 h, p  < .001), reached FEF earlier (median 6 vs. 8 days, p  = .012), had a higher rate of being fully fed in the first week of life (70 vs. 53%, p  < .035), was kept NPO for shorter duration (median 2 vs. 4 days, p  < .001), and had a higher rate of breast milk feeding at discharge (41 vs. 13%, p  < .001). There were no cases of necrotizing enterocolitis or late onset sepsis in either group during the hospital stay. Conclusion: Minimal enteral feeding during therapeutic hypothermia appears to be safe and leads to a shorter time to FEF and higher rates of breast milk feeding at discharge.